2021
DOI: 10.1016/j.tranon.2020.100926
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of Fingolimod in triple negative breast cancer preclinical models

Abstract: Highlights Fingolimod represses triple negative breast cancer cells survival in vitro by inducing cell apoptosis. Fingolimod represses triple negative breast cancer progression in orthotopic graft murine in vivo models. Fingolimod represses spleen and liver metastases without affecting lung metastasis in murine in vivo models. In contrast with Cisplatin, Fingolimod is well tolerated in murine in vivo models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 79 publications
(83 reference statements)
3
28
0
Order By: Relevance
“…Previous studies also showed that administrating cisplatin to mice significantly reduced their body weight [20][21][22]. A lower body weight in the cisplatin treatment group than in control group is also observed in breast cancer-bearing mice [23]. Accordingly in our study, the body weight was lower in the cisplatin treatment group than in the control group.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies also showed that administrating cisplatin to mice significantly reduced their body weight [20][21][22]. A lower body weight in the cisplatin treatment group than in control group is also observed in breast cancer-bearing mice [23]. Accordingly in our study, the body weight was lower in the cisplatin treatment group than in the control group.…”
Section: Discussionsupporting
confidence: 75%
“…Epidemiological studies on DMTs show data disparity 4 , although second-line immunosuppressants (azathioprine, cyclophosphamide, mitoxantrone) seem to involve a heightened risk for malignancy 22 . However, the relationship between immunotherapy and neoplasm development is inconclusive since some of these drugs are employed as coadjuvants or even anti-cancer drugs (ALB, cladribine, mitoxantrone) ( http://www.ema.europa.eu ), or are under consideration (FLM, TER) as oncologic therapeutic options 7 , 23 . This implies their subjection by Medicines Agencies to the monitoring of the possible development of malignancy in treated MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using immunomodulating or immunosuppressive drugs is unfortunately accompanied by high risk of cancer development due to involvement of immune system in recognizing and eliminating cancer cells [182]. On the other hand, some available MS DMTs have been used for years in cancer therapy (e.g., rituximab [184], cladribine [185] and methotrexate [186]), while other current DMTs are being evaluated in the present for their anti-tumor potential (e.g., dimethylfumarate [187], fingolimod [188] and teriflunomide [189]).…”
Section: Cannabinoids and Multiple Sclerosismentioning
confidence: 99%